Adapting Experience‐Based Co‐Design to Disability Research: Co‐Producing the CycLink Co‐Design Study - John Joseph Carey; Alicia Spittle; Christine Imms; Nora Shields; Margaret Wallen; Finn O'Keefe; Miriam Joy Yates; Holly Skilbeck; Rachel Toovey (Health Expectations, 2025)
ABSTRACT Introduction Participatory methods like experience‐based co‐design (EBCD) can be used to develop complex interventions, but may need adaptations when co‐designers include young people with disability, parents and community partners. We aimed to adapt EBCD through co‐production by involving people with lived experience of disability as co‐researchers. This paper reports the co‐produced protocol and reflects on co‐researchers' contributions. Methods Guided by a six‐stage co‐production process, we formed a team of co‐researchers, academic researchers, co‐design convenors and evaluators. A five‐person steering group, comprising three co‐researchers and two academic researchers, led decision‐making and project oversight. We communicated via videoconferencing, phone and email. Briefing documents, meeting minutes and diaries supported our reflections and reporting. Results We adapted EBCD to include people with disability through creative online methods and co‐produced a two‐part ‘CycLink Co‐design Study’ protocol. Part 1 proposed using EBCD to design principles for a community cycling intervention (CycLink). Part 2 planned a mixed‐methods evaluation of our adapted EBCD. Co‐researchers influenced participant choice and accessibility by developing phased involvement options, inclusive consent processes and adapted research materials. Interpretative support during qualitative analysis improved the relevance and reflexive rigour of findings. However, resource constraints limited co‐researcher involvement in conducting EBCD activities. Conclusion Co‐production enabled us to adapt EBCD for people with diverse support needs and invite under‐represented populations (e.g., young people with childhood‐onset disability) to co‐design. Cumulative adjustments resulted from our disability expertise, guidelines and approaches facilitating co‐designers' opportunities to engage. Future studies should consider early and ongoing co‐researcher involvement within both processes. Patient or Public Contribution Two adults with disability and a parent of a young child with disability joined our team as co‐researchers. Co‐researchers valued flexible involvement, which ranged from consultative to collaborative. Co‐researchers' experiential expertise influenced the relevance of project materials and qualitative findings. We reported on co‐researcher involvement through the Guidance for Reporting Involvement of Patients and the Public Version 2 Short Form (GRIPP2‐SF) [1] (Supplemental File S1—Section A, Table S1).